Poll: Najib still prime minister of choice - News Straits, Times (New Straits Times, 2013)
KUALA LUMPUR: An opinion poll carried out in Penang, Kedah and Perlis recently showed that Datuk Seri Najib Razak is still the prime minister of choice for the majority of the people there.